PENGARUH ARUS KAS BEBAS, PROFITABILITAS, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2014 - - - Seri Murni (Universitas Islam Negeri Ar-Raniry, 2017)
This study aims to test the influence of free cash flow, profitability, firm size and leverage to the earnings managemen to non financial companies listed in Indonesia Stock Exchange in 2011-2014. There search type used in this research is hypothesis testing, by using purposive sampling method and there are 240 samples of data that become the object to be researched. The data type used is secondry data obtained from the financial statements ended on 31 December, published by the capital market reference center in the Indonesia Stock Exchange. The analysis used is multiple linear regression to test the hypothesis. The research results show that free cash flow, profitability, firm size and leverage with the same effect to nearnings management, never the less there lation partially show that (1) Free Cash Flow has significant influence toward earnings management. (2) Profitability has significant influence toward earnings management. (3) Firm Size has significant influence toward earnings management. And (4) Leverage does not have influence toward earnings management. Keywords: Free Cash Flow, Profitability, Firm Size, Leverage, and Earnings Management